Immune regulation based on sex differences in ischemic stroke pathology - Niu, Pingping; Li, Liqin; Zhang, Yonggang; Su, Zhongzhou; Wang, Binghao; Liu, He; Zhang, Shehong; Qiu, Sheng; Li, Yuntao (Frontiers in Immunology, 2023)
Ischemic stroke is one of the world's leading causes of death and disability. It has been established that gender differences in stroke outcomes prevail, and the immune response after stroke is an important factor affecting patient outcomes. However, gender disparities lead to different immune metabolic tendencies closely related to immune regulation after stroke. The present review provides a comprehensive overview of the role and mechanism of immune regulation based on sex differences in ischemic stroke pathology.